Urine of patients with early prostate cancer contains lower levels of light chain fragments of inter-alpha-trypsin inhibitor and saposin B but increased expression of an inter-alpha-trypsin inhibitor heavy chain 4 fragment - Jayapalan, J.J.; Ng, K.L.; Shuib, A.S.; Razack, A.H.A.; Hashim, Onn Haji (2013)
The present study was aimed at the identification of proteins that are differentially expressed in the urine of patients with prostate cancer (PCa), those with benign prostatic hyperplasia (BPH) and age-matched healthy male control subjects. Using a combination of 2DE and MS/MS, significantly lower expression of urinary saposin B and two different fragments of inter-alpha-trypsin inhibitor light chain (ITIL) was demonstrated in the PCa patients compared to the controls. However, only one of the ITIL fragments was significantly different between the PCa and BPH patients. When image analysis was performed on urinary proteins that were transferred onto NC membranes and detected using a lectin that binds to O-glycans, a truncated fragment of inter-alpha-trypsin inhibitor heavy chain4 was the sole protein found to be significantly enhanced in the PCa patients compared to the controls. Together, these urinary peptide fragments might be useful complementary biomarkers to indicate PCa as well as to distinguish it from BPH, although further epidemiological evidence on the specificity and sensitivity of the protein candidates is required.